Longitudinal Relations Among Parents' Reactions to Children's Negative Emotions, Effortful Control, and Math Achievement in Early Elementary School. Issue 5 (10th June 2014) - Swanson, Jodi; Valiente, Carlos; Lemery‐Chalfant, Kathryn; Bradley, Robert H.; Eggum‐Wilkens, Natalie D.
<x xml:space="preserve">Abstract</x> Panel mediation models and fixed‐effects models were used to explore longitudinal relations among parents' reactions to children's displays of negative emotions, children's effortful control (EC), and children's math achievement (N = 291; M age in fall of kindergarten = 5.66 years, SD = .39 year) across kindergarten through second grade. Parents reported their reactions and children's EC. Math achievement was assessed with a standardized achievement test. First‐grade EC mediated the relation between parents' reactions at kindergarten and second‐grade math achievement, beyond stability in constructs across study years. Panel mediation model results suggested that socialization of EC may be one method of promoting math achievement in early school; however, when all omitted time‐invariant covariates of EC and math achievement were controlled, first‐grade EC no longer predicted second‐grade math achievement.